The effect of the liquid physical properties on the wave frequency and wave velocity of co-current gas-liquid stratified two-phase flow in a horizontal pipe - Wijayanta, Setya (Elsevier Ltd, 2023)
The aim of the present study was to investigate the effect of the liquid physical properties on the liquid film thickness, wave frequency, and wave velocity in co-current gas-liquid stratified two-phase flow in a horizontal pipe. The present experimental study was conducted using an acrylic pipe with an inner diameter of 26 mm and a length of 9500 mm. The superficial velocity of liquid (JL) and gas (JG) were 0.02 m/s to 0.1 m/s and 4 m/s to 16 m/s, respectively. A highspeed video camera was used to take the visual data which is then processed by the developed image processing techniques to obtain the time series data of the liquid film thickness. The probability distribution function (PDF) and discrete wavelet transform (DWT) were used to analyze the time series of the liquid film thickness. In addition, the data were also analyzed using the power spectral density (PSD) in order to obtain the wave frequency and the wave velocity. Next, the experimental correlations to predict the wave frequency and the wave velocity were developed using the dimensional analysis. From the time series of the liquid film thickness, the effect of the viscosity and surface tension on the shifting of scale and frequency of the wavelet decomposition level, as well as the frequency and velocity of the waves were clarified. In addition, a correlation to predict the frequency and velocity of waves has been successfully developed, in which the Martinelli parameter, the ratio of gas and liquid Reynold numbers, and the Weber number play the important roles in the correlation.